Avaliação de genótipos de Brachiaria ruziziensis com e sem aplicação de silício e diferentes concentrações de CO2 sobre Collaria oleosa (Hemiptera: Miridae) - Silva, Daniela Maria (2016)
Collariaoleosa(Distant, 1883) have beenfrequently observed inpastures, and causesinjuriesto the form of the streaks on the leavesof the mainforage grassusedin Brazil.The objectives of the study were to assess the constitutive resistance of Brachiaria spp.genotypes, and the resistance induced by the application of silicon; the level of tolerance of Brachiaria spp.genotypes with and without the application of silicon, subjected to different densities of C. oleosa; and understand the direct effect of rising CO2 levels over the biology of this mirid, and indirect effect when sunjecting plants to different levels of CO2.The plants were treated with 1% of silicon (50ml of solution per kg of substrate) via soil. After 10 days of application, we assembled the first and second tests. In the first trial, the newly hatched nymphs were individualized in cylindrical plastic plates containing leaf discs of different Brachiaria spp. genotypes preserved in agar. When reaching the third instar, the nymphs were transferred to the Petri dishes. In adulthood, they were kept in cages, receiving the same food in which the nymphs developed.We used nine genotypes ofBrachiariaruziziensis,marandu (Brachiariabrizantha) and Brachiariadecumbens, evaluating the duration and survival of nymphal stage and adult longevity.In the second trial, densities of 0, 4, 8 and 16 adultC. oleosa, per plot, were maintained in two genotypes of B. ruziziensis (CNPGL BR 7 and CNPGL BR 100) and B. brizantha for a period of 10 days. Subsequently, the insects were removed, evaluating chlorophyll content, loss of chlorophyll, functional loss, damage note, dry weight and percentage of attacked leaves. In the third trial, nymphs and adult bedbugs, and the forages were subjected in phytotronin four different concentrations of CO2: 1) insects and plants subjected to 400 ppm; 2) insects subjected to 400 ppm and fed 700 ppm; 3) insects subjected to 700 ppm, and fed plants to 400 ppm, and 4) insects and forage subjectedto 700 ppm. We used two genotypes of B. ruziziensis (CNPGL BR 150, CNPGL BR 1765), in addition to B. brizantha and B. decumbens. We evaluated the duration and survival of the nymphal stage and adult longevity subjected to different treatments, using the same methodology described in the first test.The results showed that silicon does not affect the duration and survival of C. oleosa, as well as the longevity of adults at a dose equivalent to 1 t/ha. Genotypes CNPGL BR 39, CNPGL BR 43, CNPGL BR 76, CNPGL BR 97, CNPGL BR 100 and B. brizantha are resistant to C. oleosa. Regarding tolerance, silicon induced resistance in the CNPGL BR 100 genotype; concerning the genotypes not treated with silicon, the B. brizantha presented tolerance to C. oleosa. Densities superior to eight adult C.oleosacan be indicated for selection of materials resistant to this pest. When longer and shorter survival and longevity leads to a reduction in the number of generations and number of individuals, we emphasize that CNPGL BR 150 is considered the most appropriate in regions with C. oleosa. For the other genotypes/species, we expect the maintaining of the susceptibility (B. decumbens) and resistance (CNPGL BR 1765) or change in resistance (B. brizantha) for the future climate scenario.